Tuesday

September 30, 2014

September 30, 2014

Posted by **Jo** on Wednesday, January 18, 2012 at 2:58am.

f(x)=2ln(3-x)+6

- College Algebra -
**drwls**, Wednesday, January 18, 2012 at 7:53amWe don't do graphs here

- College Algebra -
**Steve**, Wednesday, January 18, 2012 at 10:38amHowever, the inverse is easily found:

If y = f(x), x = f^{-1}(y)

y = 2ln(3-x)+6

y-6 = 2ln(3-x)

(y-6)/2 = ln(3-x)

e^[(y-6)/2] = 3-x

x = 3 - e^[(y-6)/2] = f^{-1}(y)

So, f^{-1}(x) = 3 - e^[(x-6)/2]

**Answer this Question**

**Related Questions**

pre calculus - Find the inverse of the function below. Graph the function below ...

precalculus - Find the inverse of the function below. Graph the function below ...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

Math 3 - Find the inverse of the function f(x) = 5 – e^(x-1). Determine the ...

precalculus - find the inverse of the function, graph the inverse function, ...

Algebra - Myra uses an inverse variation function to model the data for the ...

Maths B - (a) What is the inverse of the function y = 3x2 ? (b) On the same set ...

college algebra - f(x)=√x-2 Find the domain of the function is it x-2 the ...

college algebra - Find the inverse of the following function. Find the domain, ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...